The Role of Teachers Islamic Boarding Schools in Training Santri's Interpersonal Skills at the Ittihadul Ummah Modern Boarding School Gontor Poso - Adawiyah Pettalongi; Muh. Nur Afwan; Mohamad Idhan (Department of Islamic Education, Postgraduate Program State Institute for Islamic Studies Palu, 2022)
This study discusses the role of Islamic Boarding Schools in training santri's interpersonal skills at the Ittihadul Ummah Gontor Poso Modern Islamic Boarding School. This study used a case study qualitative research method. Data was collected through direct observation, in-depth interviews and analysis of written documents. Then the data were analyzed with a thematic approach by building themes from the data obtained in the field. The results showed that the role of Pondok Modern Ittihadul Ummah Gontor Poso in training students' Interpersonal skills can be seen in three forms, namely in intra-curricular activities which include: 'UluumulIslamiyah, 'UluumulLughoh and 'Uluumul 'Aammah.Then the role of the pesantren is also seen in the Ko Curricular activities which include the implementation of Charity Worship. Implementation of Practice and Guidance in the formation of organizations, Scouts, and the development of interests and talents.Supervision of intra-curricular activities is carried out by teachers and administrators of the santri organization in the boarding sachool. The leadership method used in educating and training the students is direction, training, assignment, habituation, escort, and UswahHasanah.The supporting factor in training students' interpersonal skills is the support of good pesantren leaders.